Alterações de rugosidade e cor de uma resina para base de prótese submetida a um protocolo de imersão de longa duração em cinamaldeído - Macêdo, Lucas Oliveira (2021)
Introduction: Poor hygiene of acrylic resin dentures can lead to microbiological imbalance and the development of prosthetic stomatitis. Cinnamaldehyde is a phytoconstituent that has been placed as an alternative for denture disinfection due to its promising antimicrobial action. However, its possible deleterious effects on the long-term denture base materials are not known. Objective: The aim of the present study was to evaluate the effects of simulated immersion for up to five years on surface roughness and color changes of a resin thermally activated by microwave energy immersed in denture cleaning solutions. Materials and methods: Eighty disc-shaped specimens (10 x 5 mm) were made in polymethyl methacrylate (PMMA) thermally activated by microwave energy (Vipi Wave) and were immersed in four solutions (n=20): GTW –Tap water (Control); GSH - 0.5% sodium hypochlorite; GPX - Alkaline peroxide (Polish nighttime whitening); GCA - Cinnamaldehyde 27μg/mL, simulating up to five years of cleaning. Analyzes of surface roughness (Sa) and color parameters CIELab (L* a* b*, ΔEab), CIEDE2000 (ΔE00) and National Bureau of Standards (NBS) were deviated, respectively, by optical profilometry (CCI-MP, Taylor Hobson, UK) and spectrophotometry (Vita EasyShade, Vita, Germany) at four time intervals: baseline (t=0), after 104, 913 and 1825 immersion cycles. The difference between the means of the groups was verified by analysis of variance ANOVA bidirectional for repeated measures and Tukey test, with a significance level of 1% (=0.01). Results: The surface roughness was influenced by the time factor, but not by the solution factor. There was an increase in roughness Sa for all groups after 1825 cycles, with a statistically significant difference (p<0.01) when compared to the baseline, regardless of the solution studied. Regarding changes in ΔEab, ΔE00 and NBS, only the time factor was relevant in changing the color of the previous ones, with all values classified below the perceptibility and acceptability limits. The GCA group did not show roughness and color values statistically different from the other solutions tested after five years of simulated immersion (p>0.01). Conclusions: Cinnamaldehyde solution (27μg/mL) caused small changes in surface roughness and relative color parameters, similar to 0.5% sodium hypochlorite and alkaline peroxide after 5 years of simulated immersion.